Management of vertebral problems and deformities - (:unkn) unknown (Springer Milan, 2008)
Children with myelomeningocele have a high incidence of scoliosis, kyphosis and lordosis [1]. These spinal deformities are usually progressive and may cause severe disability, interfere with rehabilitation, and negate previous treatments aimed at maintaining ambulation. Spinal deformities may be congenital or acquired, specific to myelomeningocele or similar to deformities seen in other conditions. Although the majority of these deformities are paralytic and occur in childhood, as many as 15% may be congenital © 2008 Springer-Verlag Italia.